2012
DOI: 10.5152/balkanmedj.2012.012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity of Drug Resistant Mycobacterium Tuberculosis Strains in Western Turkey

Abstract: Objective: The aim of this study was to investigate the molecular diversity and clonal relationship of drug resistant Mycobacterium tuberculosis strains isolated in Western Turkey. Materials and Methods:A total of 87 strains isolated between 2006 and 2009, eight of which were rifampicin monoresistant and 79 were multidrug resistant, were analyzed with IS6110 RFLP and spoligotyping methods. Results:The results of spoligotyping showed that 7% of the strains were orphans, and 8% were undefined for family in the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…In three different studies conducted on drug-resistant and multidrug-resistant TB isolates in Turkey, the most common type was ST41 with rates of 26%, 22.5%, and 16.8%, and ST53 was the second most common with rates of 14%, 19.5%, and 15.8% (15,16,18). In our study, the rate of MDR was 3%, six of the 12 multidrug-resistant…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In three different studies conducted on drug-resistant and multidrug-resistant TB isolates in Turkey, the most common type was ST41 with rates of 26%, 22.5%, and 16.8%, and ST53 was the second most common with rates of 14%, 19.5%, and 15.8% (15,16,18). In our study, the rate of MDR was 3%, six of the 12 multidrug-resistant…”
Section: Discussionsupporting
confidence: 51%
“…Although different studies on multidrug-resistant TB isolates in Turkey have found variations in the rate of the Beijing strains between 1.3% and 50% due to differences in their patient populations, all the studies have found very high MDR ratios, varying from 41.3% to 66.7% among the Beijing strains (15)(16)(17). In a study on 4069 M. tuberculosis strains isolated in İstanbul in 2002-2005, the prevalence of the Beijing genotype was 1.1% (46/4069), the MDR rate was 12.5% (510/4069), the Beijing genotype's prevalence among multidrug-resistant TB isolates was 3.7% (19/510), MDR was found in 41.3% (19/49) of the Beijing strains, and 10 out of the 19 Beijing strains were isolated from patients who were citizens of former Soviet Union countries (17).…”
Section: Discussionmentioning
confidence: 99%
“…ln this study, Staphylococcus aureus was the most predominant bacteria this is contrary to the finding of 23 but in consonance with reports of similar studies conducted from different parts of Nigeria 24,25,26, and other country , Turkey. 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Yine ülkemizde yapılan çalışmalara baktığımızda SIT41 kümesi %23.9-7.9 (23)(24)(25)(26)(27)(28) arasında değişen oranlarda saptanmıştır. SIT41 kümesinin üç çalışmada en yaygın, iki çalışmada ise ikinci sıklıkla tespit edilen küme olduğu vurgulanmıştır.…”
Section: Discussionunclassified
“…Yaptığımız çalışmada ise SIT41 kümesi %11.6 oranında tespit edilmiş ve bu oran ile üçüncü en sık küme olarak bulunmuştur. Yapılan bu çalışmalarda Haarlem ailesi üçüncü ve dördüncü en sık tespit edilen aile olarak bildirilirken (23)(24)(25)(26)(27)(28) , bizim çalışmamızda ise bu aile ikinci en sık tespit edilen aile olmuştur (Tablo 2). Köksalan ve ark.…”
Section: Discussionunclassified